Two stages of the differentiation of HL-60 cells induced by 1α, 25 dihydroxyvitamin D3; Commitment by 1α, 25 dihydroxyvitamin D3 and promotion by DMSO. Issue 1 (January 1986) - Momoi, Takashi; Senoo, Haruki; Yoshikura, Hiroshi
Abstract : The differentiation of HL-60 cells induced by 1α, 25 dihydroxyvitamin D3 was found to be separated into two stages, i.e. commitment and promotion. Most of the HL-60 cells were committed to monocyte/macrophage lineage by pretreatment with 1α, 25 dihydroxyvitamin D3 (5–50 ng/ml) for 18–24 hr. The promotion in the second stage was inducer and lineage independent; treatment with 1.25% DMSO for 2 or 3 days promoted the differentiation of the committed HL-60 cells by 1α, 25 dihydroxyvitamin D3 into monocyte/macrophage lineage, but not granulocyte lineage.